Impact of Floor Area Ratio (FAR) on Energy Consumption at Meso Scale in China: Case Study of Ningbo. (May 2017) - Dawodu, Ayotunde; Cheshmehzangi, Ali
Abstract: In any urban planning and design project, Floor Area Ratio (FAR) of the site is a debatable factor across various stakeholders. China's increase of FAR for residential areas is one of the most remarkable cases of change of FAR in recent decades. China's urban residential projects have shifted away from low storey single-standing residential units to mid-storey mass housing projects and towards contemporary high-rise residential compounds. The changes in FAR are often very significant and is multiplied over the past few decades. In this study, FAR calculation of a meso-scale residential project located in the City of Ningbo (immediate inner city area) is put in place to shape the argument of renewable energy production and pathways towards energy use reductions. This study first elaborates on energy and policy implications of FAR. The study will then explore one example of a residential compound, based on four models of FAR (at 1, 2.5, 3 and 4). A comparison study is conducted using Eco-Tect software. All four models are analysed using their differences in heights and density. While FAR 1 is not suitable for the context of China (i.e. very low), FAR 3 and 4 are also considered to be high for energy-use reductions but are current practices. This paper argues these scenarios and concludes with impacts of FAR for energy production and reduction at meso scale.